Adult Day Services as an Essential Service and Support. (17th December 2021) - Gaugler, Joseph; Marx, Katherine; Dabelko-Schoeny, Holly; Parker, Lauren; Anderson, Keith; Albers, Elizabeth; Gitlin, Laura
Abstract: Throughout the COVID-19 pandemic, the significant challenges and gaps related to the care of older people in the U.S. were made distressingly apparent. This summary presentation will consider the effects of COVID-19 and associated shutdowns on older persons who use ADS programs, their family caregivers, and programs/staff themselves. Among recommendations to consider are the classification of adult day services and similar community-based long-term care providers as essential (and clarifying their difference from senior centers). In addition, considering new financing approaches and utilizing ADS or similar community-based programs as incubators of evidence-based innovation are options to consider to better align ADS with optimal dementia care.